Kampung Janda: Konstruksi Sosial Media Online Terhadap Perempuan yang Pernah Bersuami di Kota Banjarbaru - Aprilasari, Salma; Hakim, Arif Rahman (Huma: Jurnal Sosiologi, 2024)
The existence of public perception about the news of the nickname “widow village” in Banjarbaru City, apparently caused pros and cons in the community. This research aims to find out the social construction in online media towards “widow village”. The type of research is descriptive qualitative using a constructivism paradigm approach. Data collection used observation, interviews and documentation. Data analysis used Robert N. Entman's framing analysis model. The theories used are social construction of mass media and critical discourse analysis. The results of this study show that in the news search column delivered by online media such as Tribunnews.com, there is a regular distribution of news, varied titles and erratic release dates. After further investigation, there are only two news contents that are slightly different in the Tribunnews.com media. Meanwhile, the results of fieldwork in the dialectical process of social construction are shown in three simultaneous processes, namely internalization, objectivation, and externalization. Internalization shows how the outside community reflects the “widow village” from interactions and actions. Objectivation shows how people begin to understand what is constructed. Externalization shows how people show their views or attitudes when they have been constructed on the news of “widow village” at some time later. The conclusion that can be drawn is that some of the elements highlighted from the media's perspective are considered not only gender bias but also morality issues, such as one of the widowed female informants who is still angry and difficult to return to talking about the topic. It is important, as much as possible, to sort out which news is good and true with false or lies, don't just focus on images and news content and easily demean fellow beings, whether women or men.